A Detail Study on Biometrics with Matlab - Avinash, P; Venkateswarlu, T; Anand, Dama (International Journal of Engineering and Technology, 2018)
Biometrics is an emerging field of innovation utilizing one of a kind and quantifiable physical, natural, or behavioral attributes that can be prepared to recognize a man. It is a multidisciplinary subject that incorporates building, measurements, arithmetic, figuring, brain research, and approach. The requirement for biometrics can be found in governments, in the military, and in business applications. The Electrical Engineering Department at the U.S. Maritime Academy, Annapolis, MD, has presented a biometric flag preparing course for senior-level undergrad understudies and has built up a biometrics lab to help this course. In this paper, the creators exhibit the course content, the recently created biometric flag handling lab, and the intuitive learning procedure of the biometric course. They examine a portion of the challenges that were experienced in executing the course and how they were overcome. They additionally give some input from the course appraisal.Â Â